Designing the Production Facility Layout Using the BLOCPLAN Method (Case Study: PT Sehat Sejahtera Bersama, Jember) - Nanik, Abelina; Hariono, Budi; Hermanuadi, Didiek (P3M Politeknik Negeri Jember, 2025)
PT Sehat Sejahtera Bersama is a business that produces soy beverages. There are currently no established guidelines for equipment arrangement at the PT Sehat Sejahtera Bersama facility. The flow of industrial processes is not considered by the machines used in it. As a result, there is less space for employees to move around, and time is wasted doing repetitive tasks, making the industrial process less effective and lowering output. The blocplan technique is the approach taken to overcome this problem. The facility layout problem at PT Sehat Sejahtera Bersama can be solved using this approach by considering the final layout, material transportation distance, degree of relationship closeness, and area requirements. The area at PT Sehat Sejahtera Bersama is 244.33 m², and the total space required is 647,1 m². In the suggested layout, which is the 17th layout out of 20 possible layouts, the choice of the blocplan method is based on the R-Score value, which is almost the same or close to 1.